2012
DOI: 10.1002/acr.21559
|View full text |Cite
|
Sign up to set email alerts
|

Custom foot orthoses for rheumatoid arthritis: A systematic review

Abstract: Objective. To identify and critically appraise the evidence for the effectiveness of custom orthoses for the foot and ankle in rheumatoid arthritis. Methods. Studies were identified in appropriate electronic databases (from 1950 to March 2011). The search term "rheumatoid arthritis" with "foot" and "ankle" and related terms were used in conjunction with "orthoses" and synonyms. Included studies were quantitative longitudinal studies and included randomized controlled trials (RCTs), case-control trials, cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 37 publications
3
64
1
1
Order By: Relevance
“…Evidence from systematic reviews suggests that customised foot orthoses are sustainably effective in reducing painful foot symptoms and disability in patients with RA (39). The positive effects of foot orthoses for reducing pain and image-guided ICIs for reducing synovial hypertrophy in JIA were not demonstrated at follow-up in this study (14,17).…”
Section: Discussioncontrasting
confidence: 42%
“…Evidence from systematic reviews suggests that customised foot orthoses are sustainably effective in reducing painful foot symptoms and disability in patients with RA (39). The positive effects of foot orthoses for reducing pain and image-guided ICIs for reducing synovial hypertrophy in JIA were not demonstrated at follow-up in this study (14,17).…”
Section: Discussioncontrasting
confidence: 42%
“…In patients with RA affecting the foot, custom foot orthoses are a recommended intervention (Hennessy et al, 2012). Therefore it was hypothesized that the DPLI could provide an additional biomechanical target that may assist in the designing functionally optimized foot orthoses (Gibson et al, in press).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent research has demonstrated that abnormal foot mechanics as well as inflammatory disease factors contribute independently to the overall burden of foot disease (Barn et al, 2013;Hooper et al, 2012;. Conservative treatment options are available, with prescription footwear (Dahmen et al, 2014;Williams et al, 2007) and custom orthotic interventions (Chang et al, 2012;Hennessy et al, 2012;Woodburn et al, 2002) shown to be effective at reducing pain and peak forefoot plantar pressures.…”
Section: Introductionmentioning
confidence: 99%
“…Further, although Hennessy et al (2012) found that custom orthoses may be beneficial in reducing pain and elevated forefoot plantar pressures, they also concluded that the evidence was inconclusive for foot function, walking speed, gait parameters, and for reducing hallux valgus angle progression.…”
Section: Surgical Strategiesmentioning
confidence: 92%